Survey Research of the Reasons of People Playing Games Using the Qualitative Methods - Tony Wibowo; Vicky . (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Video games is a very major entertainment media for people nowadays. In the research, we will seek those reasons by the qualitative study which the data will be gathered with questionnaire. From the research it was found that the Game Narratives, Creative Freedom , Visual Aesthehtics and Game’s Social Connectivity game variable was the reasons of people playing games, with the latter being the main reason. The result hopefully will help game developers on how to design future games.